An evaluation of an educational intervention for improving concussion knowledge among medical students - Josheil Boparai; Chris Compton; Ryan Murray; Cole Winsor; Ashley Stringer; Mitchell Fagan; Ben Collingwood; Roger Avery (PLoS ONE, 2026)
Background There are significant gaps in concussion education in the undergraduate medical curriculum, contributing to poor concussion management in clinical practice. Objective The purpose of the current study is to evaluate the effectiveness of an educational intervention for improving concussion knowledge among undergraduate medical students. Methods An interventional pre-post study was conducted wherein participants first completed a pre-survey, followed by a didactic lecture about concussions and two post-surveys; one assessing short-term knowledge retention (within 48 hours of the lecture delivery) and long-term knowledge retention (within 2 weeks of the lecture delivery). Results A one-way ANOVA showed a statistically significant difference in concussion knowledge scores between the three time points, F(2, 156) = 77.38, p < .001, with the mean score for the pre-lecture group being significantly lower than both the immediate and the two-week post-lecture groups (p < .001). There was no statistically significant difference between the immediate and two-week post-lecture groups (p = .975, 95% CI = [−.57,  .68]), suggesting knowledge retention over time. Conclusion The improvement in concussion knowledge scores following a didactic lecture demonstrates the importance of the inclusion of teaching time dedicated to concussion education, which may in turn, contribute to improvements in clinical care and patient satisfaction.